2014
DOI: 10.7860/jcdr/2014/8533.4742
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Level Magnification on Incipient Occlusal Caries Diagnosis and Treatment Decision Making

Abstract: Introduction: This in-vitro study aimed to test the accuracy and reproducibility in detection of incipient occlusal caries and treatment decision making using unenhanced visual-tactile technique and low level magnification by the use of loupes and surgical operating microscope (SOM).Methodology: Sixty extracted human posterior teeth were assessed by two examiners using ICDAS-II index and CPI-TN probe, with and without magnification. Histopathology was used as gold standard for diagnosis of caries and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The results yet again confirm the advantage of the DOM (×3.4) magnification in facilitating a more precise diagnosis. 26 The results are similar to those of this study which found that using a DOM with (×8) magnification the diagnosis of initial carious lesions was more precise than in a direct observation.…”
Section: Observation Without Magnificationsupporting
confidence: 90%
“…The results yet again confirm the advantage of the DOM (×3.4) magnification in facilitating a more precise diagnosis. 26 The results are similar to those of this study which found that using a DOM with (×8) magnification the diagnosis of initial carious lesions was more precise than in a direct observation.…”
Section: Observation Without Magnificationsupporting
confidence: 90%
“…19 Similarly, Sisodia et al, while comparing high power magnification with microscope with low powered loupes reported sensitivity and specificity that were not different from unaided visual inspection. 18 Ari et al assessed the performance of ICDAS-II using low powered magnification with light emitting diode headlight and alternating current impedance spectroscopy device for detection of occlusal caries on primary molars and reported that with magnification, the sensitivity and specificity scores for examiners were 0.87-0.90 and 0.70-0.75, respectively, at the D1 diagnostic threshold, which is lesser than the values reported in our study. 20 But studies that were done previously, without using ICDAS scoring reported better performance with magnification.…”
Section: Discussioncontrasting
confidence: 55%
“…They reported that the intra-observer reproducibility for caries detection using surgical operating microscope ranged from average to good. 18 Yet another study by Ari et al 2013, evaluated low power magnification with LED light for ICDAS coding of occlusal caries in primary molars, reported good to excellent reproductivity. 20 On the contrary, Mitropoulos et al in 2012 compared the impact of lowpowered magnification on the detection of occlusal caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the non-magnified view enabled the visualization of the test sheet as a whole, which, in turn, allowed for more immediate identification of drilled holes and places where holes were to be drilled. However, the use of loupes limited the field of vision, despite the magnification of the orifices [ 27 ]. This factor may have caused the students to spend more time locating and focusing on the target for subsequent drilling.…”
Section: Discussionmentioning
confidence: 99%